2020
DOI: 10.3390/microorganisms8020230
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Common Mycorrhizal Networks Significantly Affects Plant Biomass and Soil Properties of the Neighboring Plants under Various Nitrogen Levels

Abstract: Common mycorrhizal networks (CMNs) allow the transfer of nutrients between plants, influencing the growth of the neighboring plants and soil properties. Cleistogene squarrosa (C. squarrosa) is one of the most common grass species in the steppe ecosystem of Inner Mongolia, where nitrogen (N) is often a key limiting nutrient for plant growth, but little is known about whether CMNs exist between neighboring individuals of C. squarrosa or play any roles in the N acquisition of the C. squarrosa population. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…These results are in agreement with Abdelhameed and Metwally (2019) and Muneer et al. (2020). The beneficial impact of AMF on maize plant growth may be due to intensifying root growth, particularly fine roots with small radius (Abou El Seoud, 2008), developing depletion area nearby the plant rhizosphere depending on the hyphae of AMF (Abou El Seoud et al., 2020; Singh and Prabha, 2020), the mycorrhizal hyphae with fine radius can enter to the soil pore space tight to plant roots (Hammer et al., 2014), and transfer nutrients to the plant, as P (Rajtor & Piotrowska‐Seget, 2016; Smith, Jakobsen, Grønlund, & Smith, 2011), excreting organic compounds (Moe, 2013), increasing root exudation (Singh and Prabha, 2020), and phosphatase enzymes (Abdelhameed & Metwally, 2019; Chen et al., 2019; Sato et al., 2019).…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with Abdelhameed and Metwally (2019) and Muneer et al. (2020). The beneficial impact of AMF on maize plant growth may be due to intensifying root growth, particularly fine roots with small radius (Abou El Seoud, 2008), developing depletion area nearby the plant rhizosphere depending on the hyphae of AMF (Abou El Seoud et al., 2020; Singh and Prabha, 2020), the mycorrhizal hyphae with fine radius can enter to the soil pore space tight to plant roots (Hammer et al., 2014), and transfer nutrients to the plant, as P (Rajtor & Piotrowska‐Seget, 2016; Smith, Jakobsen, Grønlund, & Smith, 2011), excreting organic compounds (Moe, 2013), increasing root exudation (Singh and Prabha, 2020), and phosphatase enzymes (Abdelhameed & Metwally, 2019; Chen et al., 2019; Sato et al., 2019).…”
Section: Resultssupporting
confidence: 93%
“…FUNGuild, the functional analysis of fungal communities, revealed that nutrient management practices increased the relative abundance of symbiotroph (e.g., endophyte, arbuscular mycorrhizal, and ectomycorrhizal fungi), whereas they decreased the relative abundance of plant pathotrophic fungi (e.g., plant-pathogen) compared with FFP. Generally, symbiotrophic fungi, in general, are highly helpful for the fitness, nutrition, and sustainability of most crops [ 85 , 86 , 87 ]. Pathotrophic fungi obtain nutrients by invading host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more emphasis has been given to the balanced fertilization strategy by reducing the usage of mineral fertilizers to improve crop quality, production, and uptake of nutrients [9]. The mineral fertilizers, especially nitrogen, phosphorus, and potassium, are essential for plant nutrition [10][11][12] and crop productivity [13,14]. However, an inappropriate or extensive application of fertilizers leads to severe problems of soil acidification [7,15], soil and water pollution [16,17], and greenhouse gas emissions [18,19].…”
Section: Of 13mentioning
confidence: 99%